From gut to brain: understanding the role of microbiota in inflammatory bowel disease - Wang, Siyu; Zhou, Shuwei; Han, Zhongyu; Yu, Bin; Xu, Yin; Lin, Yumeng; Chen, Yutong; Jin, Zi; Li, Yalong; Cao, Qinhan; Xu, Yunying; Zhang, Qiang; et al. (Frontiers in Immunology, 2024)
With the proposal of the "biological-psychological-social" model, clinical decisionmakers and researchers have paid more attention to the bidirectional interactive effects between psychological factors and diseases. The brain-gut-microbiota axis, as an important pathway for communication between the brain and the gut, plays an important role in the occurrence and development of inflammatory bowel disease. This article reviews the mechanism by which psychological disorders mediate inflammatory bowel disease by affecting the brain-gut-microbiota axis. Research progress on inflammatory bowel disease causing "comorbidities of mind and body" through the microbiota-gut-brain axis is also described. In addition, to meet the needs of individualized treatment, this article describes some nontraditional and easily overlooked treatment strategies that have led to new ideas for "psychosomatic treatment".